Skintight : an anatomy of cosmetic surgery - Jones, Meredith (Meredith Rachael), 1965- (Oxford ; New York : Berg, 2008)
"Skintight argues that cosmetic surgery is the most provocative and controversial aspect of a new "makeover culture". Shows such as Ten Years Younger and Extreme Makeover demonstrate that "fixing" the body is a way to improve lifestyle and uncover true identity. Meanwhile, celebrities such as Michael Jackson and Jocelyn Wildenstein demonstrate the horrors of extreme surgical alteration." "Presenting a multidisciplinary approach, and examining a wide range of popular culture case studies from women's magazines, television, architecture and the Internet among others, Skintight dissects the realities of cosmetic surgery and culture."--BOOK JACKET.
Before/after: from heresy to makeover culture -- Space and place: globalisation and mediascapes -- Morphing industries: surgeons, patients and consumers -- Stretched middle age: mothers, daughters and fairy tales -- Makeover misdemeanours: magazines and monstrous celebrities -- Sleeping beauties: Lolo Ferrari and anaesthesia -- Makeover artists: Orlan and Michael Jackson -- Transit lounges for the self.
Includes bibliographical references (p. 199-214) and index.
Keywords: Skin -- Surgery; Surgery, Plastic